Telomeric DNA sequences in beetle taxa vary with species richness - Daniela Prušáková (Nature Portfolio, 2021)
Abstract Telomeres are protective structures at the ends of eukaryotic chromosomes, and disruption of their nucleoprotein composition usually results in genome instability and cell death. Telomeric DNA sequences have generally been found to be exceptionally conserved in evolution, and the most common pattern of telomeric sequences across eukaryotes is (TxAyGz)n maintained by telomerase. However, telomerase-added DNA repeats in some insect taxa frequently vary, show unusual features, and can even be absent. It has been speculated about factors that might allow frequent changes in telomere composition in Insecta. Coleoptera (beetles) is the largest of all insect orders and based on previously available data, it seemed that the telomeric sequence of beetles varies to a great extent. We performed an extensive mapping of the (TTAGG)n sequence, the ancestral telomeric sequence in Insects, across the main branches of Coleoptera. Our study indicates that the (TTAGG)n sequence has been repeatedly or completely lost in more than half of the tested beetle superfamilies. Although the exact telomeric motif in most of the (TTAGG)n-negative beetles is unknown, we found that the (TTAGG)n sequence has been replaced by two alternative telomeric motifs, the (TCAGG)n and (TTAGGG)n, in at least three superfamilies of Coleoptera. The diversity of the telomeric motifs was positively related to the species richness of taxa, regardless of the age of the taxa. The presence/absence of the (TTAGG)n sequence highly varied within the Curculionoidea, Chrysomeloidea, and Staphylinoidea, which are the three most diverse superfamilies within Metazoa. Our data supports the hypothesis that telomere dysfunctions can initiate rapid genomic changes that lead to reproductive isolation and speciation.